Electronic Toll Collection at Parking Areas - Rastislav Pirnik; Jiri Zahradnik; Ales Janota; Peter Ciganek (Communications - Scientific letters of the University of Zilina, 2005)
The paper presents an object-oriented modeling of electronic toll collection in transport applications, deals with designing of a use case diagram, class diagram, sequence diagram, and state chart. The modelling of parking system activities by the UML language (Unified Modeling Language) creates suitable and effective environment for team members communication, simplifies software design process, and unifies principles and techniques used for documentation creation.